Complement factor H-related proteins CFHR2 and CFHR5 represent novel ligands for the infection-associated CRASP proteins of Borrelia burgdorferi - Siegel, Corinna; Hallström, Teresia; Skerka, Christine; Eberhardt, Hannes; Uzonyi, Barbara; Beckhaus, Tobias; Karas, Michael; Wallich, Reinhard; Stevenson, Brian; Zipfel, Peter F.; Kraiczy, Peter (PLOS ONE, 2010)
BACKGROUND: One virulence property of Borrelia burgdorferi is its resistance to innate immunity, in particular to complement-mediated killing. Serum-resistant B. burgdorferi express up to five distinct complement regulator-acquiring surface proteins (CRASP) which interact with complement regulator factor H (CFH) and factor H-like protein 1 (FHL1) or factor H-related protein 1 (CFHR1). In the present study we elucidate the role of the infection-associated CRASP-3 and CRASP-5 protein to serve as ligands for additional complement regulatory proteins as well as for complement resistance of B. burgdorferi. METHODOLOGY/PRINCIPAL FINDINGS: To elucidate whether CRASP-5 and CRASP-3 interact with various human proteins, both borrelial proteins were immobilized on magnetic beads. Following incubation with human serum, bound proteins were eluted and separated by Glycine-SDS-PAGE. In addition to CFH and CFHR1, complement regulators CFHR2 and CFHR5 were identified as novel ligands for both borrelial proteins by employing MALDI-TOF. To further assess the contributions of CRASP-3 and CRASP-5 to complement resistance, a serum-sensitive B. garinii strain G1 which lacks all CFH-binding proteins was used as a valuable model for functional analyses. Both CRASPs expressed on the B. garinii outer surface bound CFH as well as CFHR1 and CFHR2 in ELISA. In contrast, live B. garinii bound CFHR1, CFHR2, and CFHR5 and only miniscute amounts of CFH as demonstrated by serum adsorption assays and FACS analyses. Further functional analysis revealed that upon NHS incubation, CRASP-3 or CRASP-5 expressing borreliae were killed by complement. CONCLUSIONS/SIGNIFICANCE: In the absence of CFH and the presence of CFHR1, CFHR2 and CFHR5, assembly and integration of the membrane attack complex was not efficiently inhibited indicating that CFH in co-operation with CFHR1, CFHR2 and CFHR5 supports complement evasion of B. burgdorferi.